Proceedings, International Conference on Computer and Information Technology, December 28-29, 2001 - International Conference on Computer and Information Technology (1998- ) 2001 : University of Dhaka); University of Dhaka; Bangladesh. Ministry of Science and Technology; Bangladesh. University Grants Commission; Institute of Electrical and Electronics Engineers. Bangladesh Section (Dhaka : Dept. of Computer Science, University of Dhaka, 2001)
Contributed papers presented on the fourth year of the ongoing Conference.
"In cooperation with IEEE, Bangladesh section."
Includes bibliographical references.
Keywords: Computer science -- Congresses; Information technology -- Congresses